STRATEGI CONTENT MARKETING DALAM MENINGKATKAN KEPERCAYAAN PELANGGAN PADA LABELLA HIJAB PACIRAN LAMONGAN - Diah Laili Dwi Afrianti; Suyitno Suyitno; Ahmad Zainal Fikiri; Andi Aufa Zulal Alfudhoili; Muhammad Yani Azhar; Muhammad Agus Purnama (CAPITAL: Jurnal Ekonomi dan Manajemen, 2024)
This study aims to explore the implementation of content marketing strategies in  increasing customer trust in a women's clothing store located in Sendangagung, Paciran, Lamongan called Labella Hijab using qualitative research methods. The  content marketing strategy implemented by Labella Hijab  went well, in the type  of content marketing, Labella Hijab launched three types of content, including: Q&A, tutorials, and announcements. Labella Hijab customers meet all the characteristics of customer trust. Namely: maintaining relationships, accepting influence, being open in communication, reducing supervision, patience, providing defense, giving positive information, accepting risk, comfort, and also satisfaction. Labella Hijab has also succeeded in forming three types of Labella Hijab customer trust, including: object-benefit type, benefit-attribute, and benefit-object. Customer trust built by Labella Hijab through content marketing has increased positively.